Multi Stakeholders Partnership in the Sustainable Indonesian Palm Oil Industry: Study Case Multi Stakeholders Partnership FOKSBI - Anna Kharisma Fehmita Mubin (Journal of Governance, 2019)
As a major palm oil producer in the world, Indonesia has the duty to improve and upgrade the sustainably operational standards and pro-environment palm oil industry in accordance with the global sustainable development agenda. This is important, considering the strategic economic value of the Indonesian palm oil industry for national development and its potential strength of political economy at the international level. Critics from the international community regarding unsustainable palm oil practices, environmental degradation, deforestation, and the lack of regulation, become motivation for all stakeholders to improve Indonesian palm oil industry in all sectors and to strengthen its position at the global level. In order to move towards the spirit and ideals, the Indonesian palm oil industry adopted a governance model through a multi stakeholder partnership (MSP) FOKSBI and Indonesia Sustainable Palm Oil (ISPO). The way this Governance model provide solutions to problems and challenges of the Indonesian palm oil industry is analyzed by understanding the concept of Multi Stakeholders Partnership. Multi stakeholders partnership is able to figure out a complicated issue in the Indonesian palm oil industry since it has a characteristic of involving various actors such as government, private sectors, civil society, and international organization which can strengthen commitment and modalities of all the stakeholders in achieving common goals. Thus, coordination and sharing burden will be more directed, equal, and in accordance with their respective advantages. This study uses a qualitative method with the MSP FOKSBI case study in the Indonesian palm oil industry. The result of the study indicates that the MSP FOKSBI and ISPO have a significant part in improving the Indonesian palm oil industry, especially the fundamental transformational change towards a sustainable Indonesian palm oil industry.